Cerebral Abscess in Adult with Atrial Septal Defect and Pulmonary Stenosis - Putra GB., et al (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Cerebral Abscess in Adult with Atrial Septal Defect and Pulmonary Stenosis